OPTIMALISASI PEMETAAN DIGITAL KAWASAN MOJOSARI MELALUI APLIKASI GOGLE MAPS DALAM UPAYA MENINGKATKAN IDENTITAS DESA - Rusmini, Rusmini; Rohmi, Putri Kamilatul (Universitas Al-Falah As-Sunniyah Kencong Jember, 2025)
Mojosari Village is one of the villages located in the Sumbersuko District, Lumajang Regency. This village is situated close to the city of Lumajang and has its own unique characteristics with a distinctive rural atmosphere. However, the village is not yet well known in detail by either the local community or outsiders. Based on this situation, this study aims to optimize the digital mapping of the Mojosari area through the Google Maps application as an effort to enhance the village’s identity. There are two main research questions examined in this study: First, how is the process of optimizing the digital mapping of the Mojosari area through Google Maps carried out to strengthen the village’s identity? Second, what are the impacts of utilizing digital mapping of the Mojosari area through Google Maps in efforts to enhance the village’s identity?. The community service method used is the Asset-Based Community Development (ABCD) method. The results of the program include mapping selected places and locations to be added to Google Maps. Data were collected through interviews with six hamlet heads, observations at several locations in each hamlet, and documentation. The mapped locations include educational institutions such as TPQ, public facilities such as prayer rooms (musholla), mosques, MSMEs, landmarks like the Bullet Monument and the Cow Monument, as well as wholesale shops. Initially, several of these places and locations were not available on the map. With the implementation of digital mapping through Google Maps, these locations can now be accessed by the public and are easier to find especially for visitors or outsiders who previously had difficulty locating these important sites.